Ultrasonographic Biometrical Studies on Reproductive Organs of rbST Treated Pregnant Kundhi Buffaloes - Kachiwal, A.B.; Sheikh, B.A.; Sheikh, S.A.; Memon, K.H.; Memon, S.; Qureshi, T.A. (Journal of Buffalo Science, 2015)
Biometrical studies were conducted on sixty four gravid uteri with estimated gestation period of 1st, 2nd, 3rd and 4th month of pregnancy in Kundhi buffaloes. Sixteen specimens for each month of gestation were collected from Hyderabad slaughterhouse to evaluate techniques for measurement of reproductive organs. The measurements for fetometry and morphometry of reproductive organs by ultrasound machine and manually (by measuring tape and vernier caliper) were performed and compared. The Ultrasound examinations were performed through diagnostic ultrasound machine equipped with multi-frequency 5-10MHz transrectal linear array transducer. Analysis revealed that the ovary, foetus, foetal fluid and uterus progressively increased significantly (P<0.01) in weight during 4th month of the gestation than 1st, 2nd and 3rd month of gestation period in rbST treated Kundhi buffaloes. Ovaries with CL were significantly (P<0.01) heavier than the ovary in which CL was absent. Corpus leutum was significantly lighter (P<0.01) during 1st month of pregnancy than 2nd, 3rd and 4th month of pregnancy in rbST treated Kundhi buffaloes. Gravid uterus was significantly heavier (P<0.01) during 4th month of pregnancy than 1st, 2nd and 3rd month of pregnancy in rbST treated Kundhi buffaloes. There was no significant difference between the measurements of oviduct, cervix and vagina during 1st to 4th month of pregnancy. The placenta, foetal fluid and foetus progressively increased significantly in size as gestation period progressed. The ultrasonographic fetometric and morphometric threshold of CRL, TD and UD and foetal weight was steadily increased in rbST treated Kundhi buffaloes. There was significant increase (P<0.05) in the CRL, TD, UD and foetus weight/volume at 4th month of pregnancy than 1st , 2nd and 3rd month of pregnancy in rbST treated Kundhi buffaloes. In conclusion, the overall data indicated that the examination for ultrasonographic fetometry and morphometry of reproductive organs of kundhi buffaloes for evaluation of fetal development, estimation of gestational age and formulation of fetal chart through reproductive organs were more suitable as compare to manual biometrical evaluation